Road to Tokyo Olympic Games: do new judo rules change the technical-tactical behaviour of elite male athletes? - Barreto, L. B. M.; Aedo-Muñoz, E. A.; Soto, D. A. S.; Miarka, B.; Brito, C. J. (International Journal of Performance Analysis in Sport, 2021)
This study compared the time-motion of the combat phases in male judo within two Olympic cycles (2016 vs. 2020). We analysed of 680 combats from belonging to two Olympic cycles (340 combats 2015-2016 and 340 combats 2019-2020). The combat phase was quantified according to a validated protocol (approach, gripping, attack/defence, groundwork, and pause). The 2020 cycle athletes spent less time in the gripping (79.7 ± 50.1 vs. 104.3 ± 54.1 seconds; p ? 0.001), attack/defence (7.6 ± 5.2 vs. 9.5 ± 7.2 seconds; p ? 0.001), and groundwork phases (33.9 ± 29.0 vs. 42.2 ± 32.0 seconds; p ? 0.001), and ashorter total combat time (200.0 ± 104.6 vs. 238.0 ± 94.8 seconds; p ? 0.001) than the 2016 athletes. Additionally, the 2020 athletes had ahigher occurrence of Golden Score (0.3 ± 0.4 vs. 0.1 ± 0.2 of total combats; p ? 0.001), and ahigher time spent in the Golden Score (23.9 ± 53.5 vs. 4.1 ± 21.4 seconds; p ? 0.001). The 2016 athletes had alonger total combat time; however, the time spent on the Golden Score increased in the 2020. These results should be helpful in preparing technical-tactical training aimed at performance.